Genetic variation in the glucocorticoid pathway involved in interindividual differences in the glucocorticoid treatment. (February 2017) - Song, Qian-Qian; Xie, Wan-Ying; Tang, Yong-Jun; Zhang, Jun; Liu, Jie
Glucocorticoids (GCs) are widely used for treating asthma, rheumatoid arthritis, nephrotic syndrome, acute lymphoblastic leukemia and other autoimmune diseases. However, in a subgroup of patients, failure to respond to GCs is known as GC resistance or GC insensitivity. This represents an important barrier to effective treatment and a clinical problem requiring an urgent solution. Genetic variation in the GC pathway is a significant factor in interindividual differences in GC treatment. This article reviews the pharmacogenetics of GCs in diverse diseases based on the GC pathway.